DAMPAK KUALITAS LAYANAN DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN MEMILIH BEROBAT DI RUMAH SAKIT (Studi Kasus di Kabupaten Indragiri Hulu) - Riswidiantoro Riswidiantoro; Muji Gunarto; Joko Rizkie Rizkie Widokarti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Healthcare services are a basic need for the community, and in Indragiri Hulu Regency, there are interesting dynamics related to the competition among hospitals in attracting patients. RS Muizzah, which is a new hospital in this area, has achieved a very significant increase in patient visits compared to other hospitals. This success is believed to be due to several factors such as the new facilities and effective promotional strategies, especially through the use of social media to introduce services to the community. This phenomenon makes this research relevant in answering fundamental questions about the factors that influence patients' decisions in choosing a hospital. The quality of service and the reputation of the hospital built through electronic word of mouth become two factors that are relevant to be studied in depth. So that it can help hospitals improve their service quality and marketing strategies. The purpose of this research is to analyze the influence of service quality and electronic word of mouth on the decision to choose a hospital for treatment.This research is a descriptive quantitative explanatory study aimed at gaining an understanding of a phenomenon using survey methods with questionnaires as data collection tools and observations as the main instrument conducted on patients in 4 hospitals in Indragiri Hulu district with a population of 59,105. The sample used consisted of 100 respondents. The independent variables in this study are service quality and electronic Word of Mouth, while the dependent variable is the decision to choose treatment at a hospital. The measurement of variables was conducted using a Likert scale. Data analysis was conducted using multiple linear regression analysis and path analysis method.From the research results, it was found that the decision-making process for choosing to seek treatment at the hospital in this study is positively and significantly influenced by service quality and e-WOM, with recommendations for improvement still identifying a lack of information about the availability of doctors and the promised service schedule. In addition, improvements in healthcare facilities and a quick and accurate response to patient complaints still need to be enhanced